Cartilha educativa virtual sobre prevenção da violência sexual: promoção da saúde de pessoas cegas - Marques, Juliana Freitas (2017)
Visual impairment is considered a risk factor for sexual violence, as the disabled victim may not be able to identify the abuser, making them more vulnerable. In the perspective of promoting the health of the blind person and preventing sexual violence, we highlight the assistive technologies, considered as strategies that aim not only at the blind subject, but also at health professionals, since most of the services are from low, medium or high technological density, still has great difficulty of access and reception to the blind, leading to unfavorable conditions to the effectiveness of health promotion. Objective was to build and validate an educational primer accessible to the blind on the prevention of sexual violence. A methodological study was carried out in four stages. The first stage involved the construction of content on the prevention of sexual violence, through an integrative review of the literature that analyzed the scientific production on health promotion strategies for the prevention of sexual violence. We used the descriptors Sexual Violence and Health Promotion / Sexual Violence and Health Promotion, for searching the LILACS, PUBMED, ScIELO and CINAHL databases. Still in this stage, blind meetings were performed using the focal group technique (GF). The meetings took place in a teaching institution for the blind in the city of Fortaleza, Ceará. Data emerged from the GF were analyzed according to the technique of content analysis proposed by Bardin. The second stage of the research validated the content constructed with 9 specialists in sexual violence. The judges' assessment was analyzed using the Content Validity Index (CVI) and Cronbach's Alpha. The virtual educational primer was built following the norms and standards of accessibility for the web. The fourth and last stage performed a pilot test with 22 blinds to validate the appearance of the booklet. An Assistive Technology Assessment Questionnaire (QUATA) was used and the data were analyzed through the Statistical Package for the Social Sciences (SPSS) version 22.0, using Pearson's x2 test in the variables analysis. The research project approved by the Ethics and Research Committee of the Federal University of Ceará, with seems favorable n.º. 1.403.815. The focus group analysis showed that the blind were aware of sexual violence but did not understand the forms of prevention. The content constructed presenting IVC above 0.83 in most of the evaluated items. The booklet was built considering web accessibility standards, bringing the menu, with the links that lead to the specific content. Once constructed, it was considered validated by the target public, in which most of the items obtained adequate evaluation by the blind. There was no statistical significance in most of the correlated items, and it can be inferred that there is no difference in the accessibility of the booklet among the different blind groups. However, in the age variable presented statistical significance in the items that evaluate the stimulus to learning new contents (p = 0.036) and stimulus for behavior change (p = 0.036). Concluded that the virtual educational booklet built on accessibility standards for blind people is a viable means of information on the prevention of sexual violence.